2016
DOI: 10.1038/ncomms13007
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated NLRC4 inflammasome activation drives breast cancer progression

Abstract: Obesity is associated with an increased risk of developing breast cancer and is also associated with worse clinical prognosis. The mechanistic link between obesity and breast cancer progression remains unclear, and there has been no development of specific treatments to improve the outcome of obese cancer patients. Here we show that obesity-associated NLRC4 inflammasome activation/ interleukin (IL)-1 signalling promotes breast cancer progression. The tumour microenvironment in the context of obesity induces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(210 citation statements)
references
References 59 publications
9
195
1
5
Order By: Relevance
“…Our results indicate correlation between the infiltration of neutrophils in the primary tumor and the acquisition of a more mesenchymal phenotype by tumor cells. In contrast, Kolb and collaborators found that the inflammasome of macrophages in primary tumors in obese mice is responsible for triggering angiogenesis through expression of vascular endothelial growth factor A (VEGFA), consequently boosting primary tumor growth [10]. Our results differ in that we did not see increased macrophage content in tumors from obese mice, and we observed a reduction in vessel density with a concomitant increase in hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicate correlation between the infiltration of neutrophils in the primary tumor and the acquisition of a more mesenchymal phenotype by tumor cells. In contrast, Kolb and collaborators found that the inflammasome of macrophages in primary tumors in obese mice is responsible for triggering angiogenesis through expression of vascular endothelial growth factor A (VEGFA), consequently boosting primary tumor growth [10]. Our results differ in that we did not see increased macrophage content in tumors from obese mice, and we observed a reduction in vessel density with a concomitant increase in hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
“…The link between IL-6 and obesity is well-established (6062). In addition, transcriptomic analysis revealed marked up-regulation of IL-6 inflammatory pathway in the tumors of BC patients with obesity in comparison to those without obesity (63). In our study, we found that IL-6 increased with BW in BC patients and mice, was particularly expressed in adipose-rich regions of tumors, and was associated with worse response to anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adipocyte-secreted vascular endothelial growth factor (VEGF)-A and interleukin (IL)-1β promote tumor angiogenesis and recruitment of immunosuppressive neutrophils to the tumor microenvironment, respectively. 37,38 Given the impact of adiposity on breast cancer development and progression and the complexity of the tumor microenvironment, it is important to understand the tumor-adipose network better.…”
Section: Introductionmentioning
confidence: 99%